EST-SSR Mining and Characterization from Aquilaria malaccensis Transcriptome Shotgun Assembly - Shabrina, Hasyyati; Chaerani, Nurul; Lestari, Dini; Prasetyo, Andrie Ridzki; Fahrussiam, Fauzan (Jurnal Biologi Tropis, 2024)
Aquilaria malaccensis is a member of Thymelaceae family which is one of the main trees producing agarwood compounds in Indonesia and has high economic value. A. malaccensis has Appendix II conservation status due to high exploitation in the nature.  One of the several efforts to maintain agarwood production while also maintaining agarwood population is efficient induction by manipulation of the pathway for agarwood formation and using individuals with higher production of agarwood compounds. Selection of superior individuals can be done using molecular markers that are linked to certain genes, including microsatellites or simple sequence repeats (SSR). This study aimed to identify SSRs in the agarwood transcriptome and characterized SSR sites that are linked to genes involved in the synthesis of agarwood compounds. The transcriptome data used was extracted from the NCBI database with accession number GHJS00000000.1. SSR mining was carried out using Krait v.1.4.0 software, then BLASTed with the protein database to analyze the linkage with the related genes. Perfect SSRs were found in 0.37% of the total sequences, and compound SSRs were 10.89%. The abundance of imperfect SSR (107,043) was greater than perfect SSR (31,262), indicating that SSR in the transcriptome had a low mutation rate and the SSR site was more conserved in A. malaccensis. The SSRs that linked to genes related to agarwood synthesis including HMGR, PAL, Mevalonate Kinase, MAPK, Delta-guaiene synthase, Farnesyl pyrophosphate synthase, and Phenylalanine ammonia-lyase. The discovery of SSRs linked to these genes can be used to create molecular markers that can be applied in agarwood producing trees selection.